Knowledge, Attitude, and Practice about Fluid Consumption among Medical Students in Krida Wacana Christian University Jakarta - Luciana Budiati Sutanto; Helena Fabiani; Tasya Choiriah Putri (Jurnal MedScientiae, 2023)
Fluid is beneficial for improving cognitive, maintaining concentration, and maintaining body physiology especially for students. This study aims to have knowledge, attitude, and behaviors about fluid consumption among students in the Faculty of Medicine and Health Sciences of Krida Wacana Christian University 2019. This research design is descriptive cross sectional by using purposive sampling method to acquire subjects. The research subjects include 97 students who were qualified based on inclusion and exclusion criteria. The inclusion criteria were active PSKed batch 2019 students. The exclusion criteria students who have renal disease, fasting, consuming drugs, vitamins, or food that affects urine color. The results were categorized as good if the questionnaire percentage were 76-100%, 56-76% mediocre, and less than 56%. The results showed that most students had good knowledge about fluid consumption 81,4% while 18,6% were categorized in a mediocre group. There were no students with less knowledge. Regarding attitude towards fluid consumption, the categories were good, mediocre, and less, there were 27,8%, 71,1% and 1%. Regarding the behaviors, there were good and mediocre groups, there were 91,8% and 8,2%. In this study, the students’ knowledge and behavior about fluid consumption were very good, however, very lacking in attitude towards fluid consumption.